Energy efficiency status-quo at UK foundries: the “small-is-beautiful” project - Jolly, Mark R.; Salonitis, Konstantinos; Charnley, Fiona; Ball, Peter D.; Ahmad Mehrabi, Hamid; Pagone, Emanuele (Springer, 2017)
Energy efficiency is a critical issue for all manufacturing sectors. In the present paper the energy efficiency of UK foundries was assessed. In the context of this research 80 foundries were studied, 60 were contacted and 10 were visited. General energy data were collected using structured questionnaires, interviewing energy managers and process operators. A number of foundries are operating to a good standard, by employing energy managers and regularly auditing; they are in control of their process and working rigorously to improve their efficiency. Simultaneously though, smaller foundries have not adjusted to the new market demands and are not operating in the most energy efficient manner. Important barriers to energy efficiency in these foundries include lack of knowledge on auditing methods, poor knowledge in managing energy consumption, the inefficiency of individual process steps, production disruptions, aging equipment, personnel behavior, inadequate maintenance and lack of investment, automation and research.
Keywords: Energy efficiency; Sustainability; UK foundries